Effects of putrescine application in culture medium in improving chamomile (Chamomilla recutita (L.) Rauschert.) tolerance to osmotic stress under in vitro conditions - Saeid Fatahi; Alireza Khodabakhshzadeh; Ghader Rostami Tobnag (Advances in Horticultural Science, 2020)
In order to assess the effect of osmotic stress induced by mannitol and putrescine under in vitro conditions on some growth parameters of chamomile (Chamomilla recutita (L.) Rauschert.), treatments were arranged and compared for the main effect of osmotic stress induced by mannitol in four levels (0, 2, 4, and 6 g/l), and the interaction effect of osmotic stress*putrescine (0, 0.5, and 1 mM). Osmotic stress, especially induced by 4 and 6 g/l of mannitol, were found to significantly reduce shoot height, root length, the number of shoot and root per plant, the fresh weight of shoot, and the fresh weight of root. At 0.5 mM of putrescine added fresh weight to root, carotenoid, chlorophyll a, and chlorophyll b was increased, compared to plants grown on medium with 0 and 1 mM of putrescine. Plants grown on medium with 0.5 and 1 mM of putrescine had an increased level of flavonoid, phenolic acid, and proline under four levels of mannitol. 0.5 mM of putrescine significantly improved plant biomass and essential oil content in plants grown on medium containing 0 and 2 g/l of mannitol. The results showed that the use of putrescine could improve chamomile tolerance to osmotic stress.